Opposing Epigenetic Signatures in Human Sperm by Intake of Fast Food Versus Healthy Food - Soubry, Adelheid; Murphy, Susan K.; Vansant, Greet; He, Yang; Price, Thomas M.; Hoyo, Cathrine (Frontiers in Endocrinology, 2021)
Animal experiments have demonstrated that diets high in fats create a harmful environment for developing sperm cells, contributing to impaired reproductive health and induced risk for chronic diseases in the next generation. Changes at the level of the epigenome have been suggested to underlie these observations. Human data are limited to verify this hypothesis. We earlier demonstrated a link between male obesity and DNA methylation changes at imprinted genes in mature sperm cells and newborns, but it is currently unknown if a paternal eating pattern could also be related to indices for epigenetic inheritance. We here aim to examine a yet unexplored link between consumption of healthy or unhealthy foods and methylation at imprint regulatory regions in DNA of sperm. We obtained semen and data from 67 men, as part of a North Carolina-based study: The Influence of the Environment on Gametic Epigenetic Reprogramming (TIEGER) study. Dietary data included intake of fruits/nuts, vegetables/soups, whole grain bread, meat, seafood/fish, and fatty or processed food items. Multiple regression models were used to explore the association between dietary habits and clinical sperm parameters as well as DNA methylation levels, quantified using bisulfite pyrosequencing at 12 differentially methylated regions (DMRs) of the following imprinted genes: GRB10, IGF2, H19, MEG3, NDN, NNAT, PEG1/MEST, PEG3, PLAGL1, SNRPN, and SGCE/PEG10. After adjusting for age, obesity status and recruitment method, we found that Total Motile Count (TMC) was significantly higher if men consumed fruits/nuts (β=+6.9,SE=1.9,p=0.0005) and vegetables (β=+5.4,SE=1.9,p=0.006), whereas consumption of fries was associated with lower TMC (β=-20.2,SE=8.7,p=0.024). Similarly, our sperm epigenetic analyses showed opposing associations for healthy versus unhealthy food items. Frequent consumption of fries was related to a higher chance of sperm being methylated at the MEG3-IG CpG4 site (OR=1.073, 95%CI:1.035-1.112), and high consumption of vegetables was associated with a lower risk of DNA methylation at the NNAT CpG3 site (OR=0.941, 95%CI:0.914-0.968). These results remained significant after adjusting for multiple testing. We conclude that dietary habits are linked to sperm epigenetic outcomes. If carried onto the next generation paternal unhealthy dietary patterns may result in adverse metabolic conditions and increased risk for chronic diseases in offspring.